Intracranial hemorrhage detected through a craniotomy site with point of care ultrasound. Issue 3 (18th June 2021) - Zakharchenko, Svetlana; Hansen, Allyson; Ibikunle, Aminat; Devasagayaraj, Richard; Charles, Patrick
Abstract: A 60‐year‐old male presented to the emergency department with acute change in mental status while recovering from a recent hemicraniectomy. During evaluation by the emergency physician, a point‐of‐care ultrasound (POCUS) was performed using the patient's existing craniectomy site as a sonographic window. Multiple areas of intracranial hemorrhage were visualized on POCUS and head computed tomography scan ultimately requiring urgent neurosurgical intervention. Our case report demonstrates an innovative application of POCUS in the emergency department‐ setting that has potential to expedite diagnosis and management of life‐threatening neurosurgical etiologies, such as hemorrhage and midline shift, in a unique patient population.